Hubungan Sarapan dengan Risiko Obesitas pada Anak di SDN X Jakarta - Nourmayansa Vidya Anggraini; Afdila Afdila (MAHESA : Malahayati Health Student Journal, 2023)
ABSTRACT A preliminary study at SDN X Jakarta as many as 5 students had breakfast <4x/week and nutritional status obesity, 2 students had breakfast <4x/week and normal nutritional status, 2 students had breakfast >4x/week have normal poor nutrition nutritional status, and 1 student who eats breakfast <4x/week has underweight nutritional status. Nutrition plays a role as a supporter of health aspects. Skipping breakfast is closely linked to an increased risk of obesity-associated with dietary elements.Relationship between breakfast habits and the risk of obesity in school-age children at SD Negeri Rorotan 01 Pagi as an effort to reduce the incidence of obesity and avoid degenerative diseases in adulthood. The method used in this research is quantitative with the type of Analytic Cross-Sectional Study. The sampling technique used in this study is multistage sampling, where the researcher first uses a purposive sampling technique to determine the number of students at risk of obesity, then uses a simple random sampling technique. The results of the chi-square test analysis showed that there was a relationship between breakfast habits and the risk of obesity (p-value <0.05). It is hoped that families or parents can pay attention to their child's nutritional intake, especially at breakfast, and look for a lot of information about balanced nutrition in children. There is a relationship between breakfast and the risk of obesity in school-age children at SDN X Jakarta with p-value 0.047 (p value < 0.05) and OR¬ = 0.4 (95% CI; 0.2-0.9) which means that students with poor breakfast habits have a risk of obesity of 0.4 times. Keywords: Breakfast, Children, Obesity Risk  ABSTRAK Studi pendahuluan di SDN X Jakarta sebanyak 5 siswa sarapan <4x/minggu dan status gizi obesitas, 2 siswa sarapan <4x/minggu dan status gizi normal, 2 siswa sarapan >4x/minggu normal miskin status gizi gizi, dan 1 siswa yang makan pagi <4x/minggu berstatus gizi kurang. Gizi berperan sebagai pendukung aspek kesehatan. Melewatkan sarapan terkait erat dengan peningkatan risiko obesitas terkait dengan unsur makanan. Hubungan kebiasaan sarapan pagi dengan risiko obesitas pada anak usia sekolah di SD Negeri Rorotan 01 Pagi sebagai upaya menurunkan kejadian obesitas dan menghindari penyakit degeneratif di masa dewasa. Metode yang digunakan dalam penelitian ini adalah kuantitatif dengan jenis Analytic Cross-Sectional Study. Teknik pengambilan sampel yang digunakan dalam penelitian ini adalah multistage sampling, dimana peneliti terlebih dahulu menggunakan teknik purposive sampling untuk menentukan jumlah siswa yang berisiko obesitas, selanjutnya menggunakan teknik simple random sampling. Hasil analisis uji chi-square menunjukkan bahwa ada hubungan antara kebiasaan sarapan pagi dengan risiko obesitas (p-value<0,05). Diharapkan keluarga atau orang tua dapat memperhatikan asupan gizi anaknya terutama pada saat sarapan pagi, serta banyak mencari informasi tentang gizi seimbang pada anak. Ada hubungan sarapan pagi dengan risiko obesitas pada anak usia sekolah di SDN X Jakarta dengan p-value 0,047 (p value < 0,05) dan OR¬ = 0,4 (95% CI; 0,2-0,9) yang berarti bahwa siswa dengan kebiasaan sarapan yang buruk memiliki risiko obesitas sebesar 0,4 kali. Kata Kunci: Sarapan, Anak-Anak, Risiko Obesitas